Surface modification of biomaterials based on high-molecular polylactic acid and their effect on inflammatory reactions of primary human monocyte-derived macrophages: perspective for personalized therapy - Stankevich, Ksenia; Gudima, Alexandru; Klüter, Harald; Kzhyshkowska, Julia (Materials science & engineering. C, Materials for biological applications, 2015)
Polylactic acid (PLA) based implants can cause inflammatory complications. Macrophages are key innate immune cells that control inflammation. To provide higher biocompatibility of PLA-based implants with local innate immune cells their surface properties have to be improved. In our study surface modification technique for high-molecular PLA (MW=1,646,600g/mol) based biomaterials was originally developed and successfully applied. Optimal modification conditions were determined. Treatment of PLA films with toluene/ethanol=3/7 mixture for 10min with subsequent exposure in 0.001M brilliant green dye (BGD) solution allows to entrap approximately 10−9mol/cm2 model biomolecules. The modified PLA film surface was characterized by optical microscopy, SERS, FT-IR, UV and TG/DTA/DSC analysis. Tensile strain of modified films was determined as well. The effect of PLA films modified with BGD on the inflammatory reactions of primary human monocyte-derived macrophages was investigated. We developed in vitro test-system by differentiating primary monocyte-derived macrophages on a coating material. Type 1 and type 2 inflammatory cytokines (TNFα, CCL18) secretion and histological biomarkers (CD206, stabilin-1) expression were analyzed by ELISA and confocal microscopy respectively. BGD-modified materials have improved thermal stability and good mechanical properties. However, BGD modifications induced additional donor-specific inflammatory reactions and suppressed tolerogenic phenotype of macrophages. Therefore, our test-system successfully demonstrated specific immunomodulatory effects of original and modified PLA-based biomaterials, and can be further applied for the examination of improved coatings for implants and identification of patient-specific reactions to implants.
Gesehen am 17.12.2018
Available online 26 February 2015